Analysis of the Disappearance Curve of Labelled Fibrinogen at the Time of Hyperfibrinogenemia in Rabbits with Acute or Chronic Intravascular Coagulation - Hasegawa, H; Watanabe, N; Nagata, H; Murao, M (Thrombosis and Haemostasis, 1976)
In order to study fibrinogen metabolism, the disappearance curve of 125I-labelled homologous fibrinogen was investigated in the rabbits with experimentally induced acute or chronic intravascular coagulation by injection of Lycopodium spores or thromboplastin. The results obtained were as follows.1. Using haemolysate, an intermediate phase with upward convexity was clearly recognized between the early rapid-decay phase and the late slow phase in each radioactivity decay curve obtained in groups of rabbits. This convexity was most marked with acute intravascular coagulation induced by injection of Lycopodium spores, and was less marked, although higher, with chronic intravascular coagulation induced by injection of thromboplastin than that in the normal control.2. The disappearance curve with the intermediate phase could be expressed, in approximation, as a sum of 2 equations - the initial exponential decay equation and the late parabolic one.3. From the results obtained by separate examinations of the disappearance curve of plasma, fibrin clots and serum in rabbits with acute intravascular coagulation induced by injection of Lycopodium spores, the intermediate phase appears to be influenced more by the secondary increase of labelled non-clottable part than recirculation of the labelled fibrinogen.4. The half time (27.4 hours) of the radioactivity in fibrin clots at the late phase observed in the group of rabbits with acute intravascular coagulation induced by injection of Lycopodium spores was shorter than that in the normal rabbits (50.2 hours). This fact may indicate that the increase of fibrinogen in the group of rabbits with acute intravascular coagulation induced by the injection of Lycopodium spores is due to overproduction of fibrinogen.5. The half time of labelled fibrinogen should be calculated from disappearance curve of fibrin clots, instead from that of haemolysate or plasma.